Penerapan Perawatan Luka Pada Area Insisi Untuk Mengatasi Resiko Infeksi Pasien Yang Mengalami Post Op Sectio Caesarea Di Rumah Sakit Bhayangkara Makassar - Andi Suriyani; Fardi (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
Cesarean section (sectio caesarea) is a surgical procedure that penetrates a mother's abdomen to deliver one or more babies, commonly referred to as laparotomy and hysterotomy. Therefore, cesarean delivery is also known as artificial childbirth. According to data from the Medical Records of Bhayangkara Hospital Makassar, the number of cesarean section deliveries in 2021 was 314 (93.1%) for inpatient care and 23 (6.8%) for outpatient care. In 2022, there were 201 (25.5%) inpatient cases and 586 (74.4%) outpatient cases. The objective of this study is to examine the implementation of incision area care and evaluate its effectiveness in addressing the risk of infection at Bhayangkara Hospital Makassar. Before the intervention, the assessment of Mrs. D, a 28-year-old patient in the Nuri Ward of Bhayangkara Hospital Makassar, showed increased pain with a severity scale of 7 (severe) and redness around the incision area. However, after three consecutive days of incision area care intervention, the results showed a reduction in pain to a scale of 2 (mild), and the redness around the incision area also decreased.